Ocena dendrologiczna i krajobrazowa parku wiejskiego Borek (woj. lubelskie) - Kaczmarski, Zdzisław; Dobrowolska, Dorota (Leśne Prace Badawcze, 2016)
This article presents the results of my research conducted in the rural park Borek, which is located in Gardzienice Drugie, Lublin province. The study was comprised of measuring the dendrological value of the park using the Rokosza method and determining the landscape’s aesthetic value using the scenic beauty estimation (SBE) method. In order to establish the dendrological and aesthetic values, the park was divided into four sections, which were then compared with each other. It has been shown earlier that results of the scenic beauty estimation method and the dendrological value are only weakly correlated when it comes to park landscapes. It is therefore advisable to test the value of parks, in both categories, dendrological and aesthetic. This approach could form the basis for the development of a new method to classify and evaluate park landscapes.